Prognostic Significance of Inflammatory Markers in Patients with Oral Cavity Cancers - Erdis, Eda; Yucel, Birsen (ENT Updates, 2020)
Introduction: In the present study, we aimed to evaluate the relationship between neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR) and systemic immune inflammation index (SII) values and overall survival (OS) and disease-free survival (DFS) in patients undergoing radiotherapy (RT) with a diagnosis of oral cavity cancer (OCC). Methods: 58 patients were included who were treated with a diagnosis of OCC who applied to Cumhuriyet University Faculty of Medicine Radiation Oncology Clinic between January 2009 and December 2018. Kaplan-Meier analysis was used to determine OS and DFS. Multivariate Cox regression analysis was also performed to detect independent prognostic factors. Results: All patients had a squamous cell carcinoma (SCC) of the oral cavity composed of 50 tongue SCC and 8 buccal SCC. Cut-off values in ROC analysis: 954 [Area=0.665 (0.511-0.800), p=0.06] for SII, 174 [Area=0.659 (0.608- 0.795), p<.001] for PLR and 3.2 [Area=0.699 (0.556-0.841), p=0.016] for NLR. Prognostic factors affecting OS were SII, PLR, NLR and age. SII, NLR, PLR and grade were statistically significant prognostic factors for DFS. However, SII was an independent prognostic factor. Conclusion: In this study, high SII value was found to be an indicator of shorter OS and DFS in patients with OCC.